Effect of Psychoeducation on Mental Health among Caregivers of Patients with Chronic Kidney Disease (Jagannath University Journal of Life and Earth Sciences, 2024)
Chronic Kidney Disease (CKD) is a progressive and debilitating chronic illness that results in irreversible loss of kidney function. Nowadays, caregiving is the central role for patients who are suffering from chronic disease worldwide. Considering this, the present study was conducted to investigate the psychoeducational impact on the mental health of those who care for patients with CKD. A pre-test and post-test method of the quasi-experimental design was employed to conduct the study on a total number of 60 participants (experimental group 30 and control group 30). Participants’ age range was 18 to 59 years and mean and standard deviation were respectively 30.28 and 9.86.  An adapted Bangla version of the General Health Questionnaire-28 and Psychoeducation Materials (developed by Hossain et al., 2023) were administered to the participants. Participants were selected purposively from the National Institute of Kidney Diseases and Urology (NIKDU) of Dhaka city. The obtained data were analyzed by using descriptive statistics, mean, standard deviation, t-test, etc. Results indicate that there was a significant difference between the experimental group and the control group in mental health problems (t = 4.274, p < .05). Results also revealed that there were significant differences between the experimental group and the control group in somatic problems (t = 2.412, p < .05), anxiety and insomnia (t = 3.614, p < .05), social dysfunctions (t = 2.916, p < .05) and severe depression (t = 2.588, p < .05) among caregivers of patients with CKD. The findings of the present study indicate that after the psychoeducational training, mental health problems were better than mental health problems before the psychoeducational training. The implications of the findings have been discussed in light of research evidence from earlier research.Jagannath University Journal of Life and Earth Sciences, 9(2): 179–194, 2023 (December)